The Effect of Providing Counseling on Knowledge about Safety Houses in Housewives Neighborhood Association of Bagan Pete Village, Jambi City - Budi Aswin; Fajrina Hidayati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Potential hazard is a state or condition in a process, machine, tool, material or way of working which in an intrinsic (natural) sense can cause injury, injury, even further, namely loss of worker's life and can damage tools and the environment. The house where we live is a place that is often considered the safest and most comfortable place for us. But without us knowing it, the house is also potentially dangerous. Therefore, it is necessary to understand and be aware of the safety house for every household in minimizing the risk of work accidents that occur in the house. The purpose of this study was to analyze the effect of providing counseling on knowledge about safety houses in housewives at neighborhood association of 23, Bagan Pete Village, Jambi City. This research is a quantitative study using a quasi-experimental one group pretest-posttest design. The research population was all housewives in neighborhood association 0f 23. The research samples were 30 housewives using the purposive sampling technique. Methods of data collection through interviews using a questionnaire. Data analysis was carried out using univariate and bivariate. Bivariate analysis uses the paired T-test if the data distribution is normal, otherwise if the data distribution is free then the Wilcoxon test is used. Analysis of the data in this study used the IBM SPSS 20 application. The results of the statistical analysis showed that counseling had an effect on knowledge about safety houses (p=0.000 <0.05). The conclusion is that there is an influence of counseling on knowledge about safety house among housewives in neighborhood association of 23, Bagan Pete Jambi.Keyword: Counseling, Knowledge, Safety House